Does Foreign Ownership Affect Firm Performance? The Moderating Role of Indonesia’s Omnibus Law - Jungjungan Sitorus; Lukman Hanif Arbi (International Journal of Business Studies, 2026)
This study investigated the complex relationship between foreign ownership (FO) and firm performance, focusing on the moderating role of institutional reform in the context of Indonesia’s Omnibus Law (Job Creation Law). While prior literature suggests that foreign investors enhance performance, the impact may be conditional upon the host country's institutional quality. This research addressed this gap by analyzing different types of foreign investors (corporate and institutional) and their interaction with large-scale regulatory changes. Using a panel dataset of 147 Indonesian manufacturing firms listed on the IDX from 2018 to 2023, resulting in 882 firm-year observations, the study employed a two-way fixed effects regression model with clustered standard errors. The results indicated that overall FO, Foreign Corporate Ownership (FCO), and Foreign Institutional Ownership (FIO) did not have a significant direct impact on firm performance (ROA, ROE, and Tobin's Q). Crucially, the Omnibus Law generally failed to strengthen the FO-performance relationship. However, a significant specific finding emerged: the interaction between FIO and the Omnibus Law negatively and significantly affects Tobin's Q. This suggests that during the implementation and transition phase of major institutional reform, highly mobile foreign institutional investors became more cautious, leading the market to assign a lower valuation to FIO-held firms. The findings support Institutional Theory, emphasizing that the effectiveness of FO in enhancing corporate performance is critically dependent on the stability and maturity of the supporting institutional.